The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1177/1534582303260641
|View full text |Cite
|
Sign up to set email alerts
|

Normal Genetic Variation, Cognition, and Aging

Abstract: This article reviews the modulation of cognitive function by normal genetic variation. Although the heritability of "g" is well established, the genes that modulate specific cognitive functions are largely unidentified. Application of the allelic association approach to individual differences in cognition has begun to reveal the effects of single nucleotide polymorphisms on specific and general cognitive functions. This article proposes a framework for relating genotype to cognitive phenotype by considering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 290 publications
3
72
0
Order By: Relevance
“…Although the genetic architecture of these endophenotypes may also be somewhat complex (Flint and Munafo 2007), the expectation is that they more directly reflect the activities of neuronal mechanisms than the illness itself. Several promising polymorphisms in candidate genes associated with WM performance have already been identified in both healthy subjects and in schizophrenia patients (e.g., (Cannon 2005;Goldberg and Weinberger 2004;Greenwood and Parasuraman 2003;Parasuraman et al 2005;Wedenoja et al in press). The endophenotype strategy adopted by COGS is complementary to 20 years of genetic linkage and association studies using the clinical diagnosis of schizophrenia that have had modest success in identifying disease-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the genetic architecture of these endophenotypes may also be somewhat complex (Flint and Munafo 2007), the expectation is that they more directly reflect the activities of neuronal mechanisms than the illness itself. Several promising polymorphisms in candidate genes associated with WM performance have already been identified in both healthy subjects and in schizophrenia patients (e.g., (Cannon 2005;Goldberg and Weinberger 2004;Greenwood and Parasuraman 2003;Parasuraman et al 2005;Wedenoja et al in press). The endophenotype strategy adopted by COGS is complementary to 20 years of genetic linkage and association studies using the clinical diagnosis of schizophrenia that have had modest success in identifying disease-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…That is, DA stimulation in low span participants made both their brain activation and performance more like that of high span participants. Individual differences in WM span and underlying PFC function are, at least in part, related to genetic differences, particularly, the possession of certain polymorphisms of genes which impact on DA activity in PFC (such as COMT, MAOA, DRD4, and DAT-1, e.g., Blasi et al, 2005;Diamond et al, 2004;Fan et al, 2003;Greenwood and Parasuraman, 2003;Parasuraman et al, 2005). For example, in the Rueda et al (2005) study, children with the pure long homozygous DAT-1 allele showed better performance on tests of attention and intelligence than those with the heterozygous alleles.…”
Section: Item-specific Versus Process-specific Effects In Working Memorymentioning
confidence: 99%
“…Greenwood & Parasuraman, 2003). Greenwood and Parasuraman point to the variable heritability of a number of cognitive functions.…”
Section: Genetic Factors In Cognitive Function and Neural Structurementioning
confidence: 99%